Structure of adenosine deaminase mRNAs from normal and adenosine deaminase-deficient human cell lines. - Adrian, G S (1984)
The structure of human adenosine deaminase mRNA from normal and mutant lymphoblasts was examined by sequence analysis of a cDNA for normal mRNA and electrophoretic analyses of DNA fragments generated by S1 endonuclease cleavage of mRNA-cDNA hybrids. The 1,533-base sequence of the cloned cDNA represents the complete mRNA sequence with the possible exception of some of the 5' untranslated region. S1 nuclease analyses of hybrids between cloned cDNA and normal adenosine deaminase mRNA confirmed that a 76-base sequence in a previously examined adenosine deaminase cDNA is an intron. S1 nuclease analyses of mRNAs from seven mutant cell lines demonstrated that four of the mutants, those in the GM-2471, GM-2756, GM-4258, and GM-2606 cells, contain small defects, such as single-base changes, that are not detectable by the S1 nuclease technique. Three of the mRNAs, those in GM-3043, GM-2294, and GM-2825A cells, do contain defects detectable with S1 nuclease. These defects differ from each other and have been mapped to specific regions of the mRNA. Some or all of these defective mRNAs are postulated to result from anomalous RNA processing.